2011
DOI: 10.1002/bjs.7305
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional predictors of postoperative outcome in pancreatic cancer

Abstract: The PNI is associated with overall survival and postoperative complications, in particular pancreatic fistula, in patients with pancreatic cancer. The moderate accuracy of PNI as a predictor of survival limits its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
368
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(410 citation statements)
references
References 36 publications
11
368
2
4
Order By: Relevance
“…Recent studies have reported the prognostic significance of the preoperative inflammation-based scores, such as the GPS, the neutrophil to lymphocyte ratio (23), the platelet to lymphocyte ratio (24), the Prognostic index (25), and the Prognostic nutritional index (26). An inflammatory response to the tumor leads to tumor proliferation and metastasis due to inhibition of apoptosis and promotion of angiogenesis (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the prognostic significance of the preoperative inflammation-based scores, such as the GPS, the neutrophil to lymphocyte ratio (23), the platelet to lymphocyte ratio (24), the Prognostic index (25), and the Prognostic nutritional index (26). An inflammatory response to the tumor leads to tumor proliferation and metastasis due to inhibition of apoptosis and promotion of angiogenesis (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative albumin levels and prognostic nutrition index (PNI) have been shown to be independent factors to predict POPF. Serum albumin level of < 4.0 g/dl and a PNI of < 45 is associated with significantly higher incidence of fistula (37.5 % versus 18.7 % and 40 % versus 22 % respectively) [37]. Patients with higher BMI (>25 kg/m 2 ) are associated with an increased risk of POPF [38,39].…”
Section: Patient Factorsmentioning
confidence: 96%
“…There were also many studies reporting that haematological markers of systemic inflammatory response such as white blood cell count or its components (neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR)), platelet, and platelet-lymphocyte ratio (PLR) are also prognostic indicators for cancer clinical outcomes (Yamanaka et al, 2007;Cho et al, 2009;Kishi et al, 2009;Sarraf et al, 2009;Kwon et al, 2012;Dalpiaz et al, 2013;Fox et al, 2013). In addition, other inflammatory factor combinations such as Prognostic Index (PI) and Prognostic Nutritional Index (PNI) have also been linked with prognosis of malignancies (Kasymjanova et al, 2010;Nozoe et al, 2010;Kanda et al, 2011). However, the value of these markers as independent prognostic factors and the extent these markers improve prognostic classification for patients with inoperable advanced or metastatic GC receiving first-line chemotherapy remains uncertain.…”
Section: Introductionmentioning
confidence: 99%